Zwierzęta jako ofiary przemocy domowej - Helios, Joanna; Jedlecka, Wioletta (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
Domestic violence is often accompanied by the phenomenon of violence against animals. Its victims are mostly pets and it usually occurs in the form of bullying. Criminal law does not treat crimes against animals as violent crimes, which makes them “silent” victims of domestic violence. The considerations contained in this sketch have been devoted to injured animals.
Keywords: cruelty; domestic violence; violence against animals; bullying; aggression